Nanostructured materials for protection and reinforcement of timber structures: A review and future challenges. (30th October 2015) - Marzi, Tanja
Highlights: Nanostructured materials offer potential applications in timber structures. Recent nano-materials for reinforcement and protection of timber are examined. Innovative nano-coatings and their wood surface protection functions are reviewed. Next-generation application fields have also been analysed. Research on reinforcement of timber structures with carbon nanotubes is presented. Abstract: The latest technological innovations in nanostructured materials for reinforcement and protection of timber structures are presented. Starting from the definition of nanotechnologies applied in the construction field, the paper briefly describes nano-materials already existing on the market, nano-coatings and their wood surface protection functions, classification and compatibility with the different wood species, focusing on their potential usage and their application in the fields of architecture, civil engineering and cultural heritage. Next-generation application fields are reviewed with a special focus on an experimental research on reinforcement of historic timber structures with the application of a polymeric resin reinforced with carbon nanotubes.